Geographic distribution of C4 species and its phylogenetic structure across China - Zhang, Aiying; Yang, Zhongjie; Zuo, Yu; Ma, Liang; Zhang, Hanyu (Frontiers in Plant Science, 2023)
Over the past fifty years, the distribution patterns of C4 species, across large spatial scales are largely ignored. Here, we endeavored to examine patterns in the taxonomic and phylogenetic diversity of species with C4 photosynthetic pathways across the broad spatial extent of China, and relate those to climatic gradients. We built a database of all plants with the C4 photosynthetic pathway in China. We analyzed the geographic distributions, taxonomic diversity, phylogenetic diversity, and phylogenetic structure of all C4 species, as well as the three families with the most C4 species (Poaceae, Amaranthaceae and Cyperaceae), and compared their values along temperature and precipitation gradients at two scales—the level of the province and at the 100 x 100 km grid cell. We found 644 C4 plants (belonging to 23 families 165 genera) in China, with Poaceae (57%), Amaranthaceae (17%), Cyperaceae (13%) accounting for the majority of species. Standardized effect size values of phylogenetic distances were negative overall, indicating that C4 species showed a phylogenetic clustering pattern. Southern China had the highest species richness and the highest degree of phylogenetic clustering. C4 tended to be more phylogenetically over-dispersed in regions with colder and/or drier climates, but more clustered in warmer and/or wetter climates. Patterns within individual families were more nuanced. The distribution of C4 species and its phylogenetic structure across China was constrained by temperature and precipitation. C4 species showed a phylogenetic clustering pattern across China, while different families showed more nuanced responses to climate variation, suggesting a role for evolutionary history.